Effect on particulate and gas emissions by combusting biodiesel blend fuels made from different plant oil feedstocks in a liquid fuel burner - Abdul Rahim, Norwazan (MDPI AG, 2016)
This paper focuses on the combustion performance of various blends of biodiesel fuels and diesel fuel from lean to rich mixtures. The biodiesel blend fuel combustion experiments were carried out using a liquid fuel burner and biodiesel fuel made from various plant oil feedstocks, including jatropha, palm and coconut oils. The results show that jatropha oil methyl ester blend 25 (JOME B25) and coconut oil methyl ester blend 25 (COME B25) blended at 25% by volume in diesel fuel produced lower carbon monoxide (CO) and unburned hydrocarbon (UHC) emissions due to more complete combustion. Overall, JOME B25 had the highest CO emission reduction, at about 42.25%, followed by COME B25 at 26.44% emission reduction relative to pure diesel fuel. By contrast, the palm oil methyl ester blend 25 (POME B25) showed a 48.44% increase in these emissions. The results showed that the nitrogen oxides (NOx) emissions were slightly higher for all biodiesel blend fuels compared with pure diesel fuel combustion. In case of sulphur dioxide (SO2) and UHC emissions, all biodiesel blends fuels have significantly reduced emissions. In the case of SO2 emission, the POME B25, JOME B25 and COME B25 emissions were reduced 14.62%, 14.45% and 21.39%, respectively, relative to SO2 emission from combusting pure diesel fuel. UHC emissions of POME B25, JOME B25 and COME B25 showed 51%, 71% and 70% reductions, respectively, compared to diesel fuel. The conclusion from the results is that all the biodiesel blend fuels are suitable and can be recommended for use in liquid fuel burners in order to get better and 'greener' environmental outcomes.